A Study on Highly Sensitive C-Reactive Protein (Hs-CRP) in Patients with Bronchial Asthma (Delta Medical College Journal, 2018)
Background: Asthma is a chronic inflammatory disorder of the airways. Relevance of highly sensitive C-reactive protein (hs-CRP), an acute phase reactant and a sensitive marker of low-grade systemic inflammation in bronchial asthma has not been fully studied.Objectives: Reported studies have found an inverse relationship between lung function and markers of systemic inflammation. The aim of this study was to clarify the relationship between serum level of hs-CRP and bronchial asthma.Materials and method: In this study, hs-CRP was measured in 60 patients with asthma and 40 healthy control subjects. Of all asthmatics, 39 patients had partially controlled and uncontrolled asthma and 21 patients had asthma during exacerbation.Results: Highly sensitive CRP was significantly higher (p